PERAN GURU IPS DALAM MENINGKATKAN PENDIDIKAN KARAKTER MANDIRI PADA PESERTA DIDIK KELAS VIII SMP NEGERI 7 KOTA CIREBON - Kamiliya Rahman; Ratna Puspitasari; Wisnu Hatami (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2023)
This study aims to determine the independent character of seventh-grade students, the obstacles experienced by Social Sciences teachers in the process of forming independent characters, and to find out the role of the Social Sciences teacher in forming and enhancing the independent character in Social Studies learning that has been carried out so far. This type of research uses a qualitative research approach with a descriptive type. The research subjects were social studies teachers for grade seven, deputy head of curriculum, and seventh-grade students of class VIII A. The data sources here used primary and secondary data. Data collection techniques carried out included observation, interviews and documentation studies and giving questionnaires for students' independent character instruments. Data analysis includes data reduction, data presentation and drawing conclusions. Data validity using data triangulation. Based on research results, it is known that forming independent character for class VIII students is difficult and easy. There are many factors behind it, especially internal and external factors of students. The role played by social studies teachers in increasing independent character is by using lesson plans with elements of independent character, using media and tools that contain independent character. Through habituation of the personal attitudes or behavior of social studies teachers become role models for these students.